Madrasah Education in Secular, Modern and Multicultural Singapore: Challenges and Reform - Helmiati Helmiati (TSAQAFAH, 2021)
Madrasah education has become a major concern for Singapore government due to the characteristic of Singapore as a secular, modern and pluralist state, coupled with the government’s deep-seated anxiety whether the Islamic school graduates can contribute to national economy and integrate into national cohesion. This article aims at exploring the challenges and reform of madrasah education within the secular, modern and multicultural state. Collecting data from official documents and websites, literature review, and interviews, this study is qualitative in which some data and relevant literatures have been presented and analyzed. It finds that madrasah education has constantly been perceived in a negative nuance due to its ineffective contribution to the knowledge-based economy. The orthodox and conservative education system in the Islamic institution of education is also viewed to hinder Singapore’s racial and religious cohesion. These then force Muslims to reform the Muslim school by changing orientation, revamping the system, improving quality, instilling national cohesion and fundraising. This study implies that reformation in Islamic education would be successful by innovatively negotiating the pressures that national politics and rule present and appealing to the identity and aspiration of local society.